HISTORIOGRAFI AKUNTANSI INDONESIA MASA MATARAM KUNO (ABAD VII-XI MASEHI) - Lutfillah, Novrida Qudsi; Sukoharsono, Eko Ganis (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Abstract. Historiography of Indonesian Accounting in The Ancient MataramÂ Kingdom Era (VII-XI Century). Historiography or historical writing in the history of scienceis the culmination of the entire history of the research activities. Historiography accounting in Indonesia can be seen in the study of accounting history of the Singosari Kingdom (1222-1292) and the study of accounting history during the reign of King Udayana, Bali (989-1011). This study used social archeology method as an analytical tool to explore the accounting historiography in the Ancient Mataram Kingdom (8-11 centuryAD), focusing on Taxation Accounting. Recording and reporting activities of taxation as the royal income indicates that the activity occurs contains the value of âSepi ing Pamrih, Rame ing Gawe